Developing the Scholarship of Teaching and Learning at the McMaster Institute for Innovation and Excellence in Teaching and Learning. (1st June 2016) - Marquis, Elizabeth; Ahmad, Arshad
Abstract : This chapter describes three research‐informed SoTL initiatives undertaken at the McMaster Institute for Innovation and Excellence in Teaching and Learning and presents preliminary evidence of their impact on teaching, learning, and SoTL.